Cross-cultural nuances of the sources and consequences of subjective feelings of unsafety: A qualitative analysis in four cities. (October 2019) - Valente, Riccardo; Crescenzi Lanna, Lucrezia
The research aims at analyzing the fear of crime and its consequences on social cohesion and informal social control. The study is based on data collected through a triangulation of qualitative techniques (in-depth interviews, participant observation, and semi-structured focus groups) throughout eight neighborhoods of four European cities. Challenging the initial expectations, the results obtained show that, under certain circumstances, the fear of crime might foster genuine forms of social involvement and problem-solving participation. Nevertheless, the general trend indicates that crime-related anxieties are fueling the emergence of nostalgic, passive-aggressive, and violent forms of identity, which might promote potentially dangerous types of collective action.